Acinetobacter johnsonii Peritonitis in a Patient on Peritoneal Dialysis: A Case Report and Review of the Literature - Srigyan, D; Gautam, Hitender; Mohapatra, S; Sood, S; Kapil, A; Das, BK (Nepal Medical College Journal, 2020)
Acinetobacter species have important role in modern medicine due to their increasing presence in health-care facilities and antibiotic resistance. They are non-fermentative, aerobic, Gram-negative coccobacilli and are important bacteria causing peritonitis in patients on peritoneal dialysis. Acinetobacter johnsonii is widely found in the aquatic environment and animals. Peritonitis caused by A. johnsonii is rarely encountered and reported. Here we report a case of A. johnsonii peritonitis in a patient on peritoneal dialysis. To the best of our knowledge, this is the first case of peritoneal dialysis-associated peritonitis by A. johnsonii reported from India.